O lugar do desenho no século XX: dimensões e conceito - Bamonte, Joedy Luciana Barros Marins [UNESP] (My University, 2012)
The following work proposes an approach to drawing based upon a language which is diluted and also introduced in the hybridization perceived in the 21st Century. Based on a shift of languages in visual arts which refers to appropriations and to the expansion of possibilities for the procedure and the physicality of the artistic work, it looks into the place of drawing, its dimensions and concepts. While it is an expressive vehicle, the drawing constitutes an indispensable element for the development of expression forms, transformed and diversified over centuries. In the 21st Century, its plurality presents it in several dimensions. When it is expanded in the space, it not only makes sure that it not bi dimensional, as well as it is asserted in its essence, besides coded methods. The text is structured around theoretical and practical researches based on Ostrower, Derdyk, Canclini and author/artist.

O presente trabalho propõe uma abordagem sobre o desenho como linguagem diluída e inserida no hibridismo presente no século XXI. Com base em um deslocamento das linguagens nas artes visuais que remete a apropriações e à expansão de possibilidades para o procedimento e a fisicalidade da obra artística, investiga-se o lugar do desenho, suas dimensões e conceito. Enquanto veículo expressivo, o desenho constitui elemento imprescindível para o desenvolvimento de formas de expressão, transformadas e diversificadas no decorrer dos séculos. No século XXI, sua pluraridade o apresenta em dimensões diversas e ao ser expandido no espaço. Não somente deixa a bidimensionalidade, como também é reafirmado em sua essência, além de métodos codificados. O texto é estruturado a partir de pesquisas teórica-práticas com base em Fayga Ostrower, Edith Derdyk, Néstor Canclini e obras da autora/artista.
Keywords: Drawing; Hybridity; Contemporary art; Space; Visual arts; Desenho; Hibridismo; Arte contemporânea; Espacialidade; Artes visuais